Rice Yield Improvement by Sugarcane Filter Cake Fertilizer Application in the Protected Dyke - Vo Quang Minh; Le Van Khoa; Nguyen Thi Phuong Dai (International Journal of Agronomy)
This study was carried out to evaluate the fertility of rice soil and the effect of inorganic fertilizers combined with sugarcane filter cakes on rice yield in a protected dike area in Cho Moi district, An Giang province. The experiment consists of 4 treatments, and the dose of fertilizer in each treatment is (1) controlled according to the farmers’ dosage (224 kg N + 148 kg P2O5 ha−1), (2) fertilize according to farmers + 6 tons/ha of cow manure composted with straw, (3) fertilizer according to farmers + 6 tons/ha of cow manure composted 15 cm deep, and (4) fertilize according to farmers + 2 tons/ha of organic fertilizer with sugarcane filter cakes. By analyzing the nutrient content of soil samples, it was found that inorganic fertilizers in combination with sugarcane residues improved soil fertility as reduced soil acidity and electrical conductivity, and increased organic matter, total nitrogen content, and exchangeable K. In addition, exchange and enriched exchangeable Mg achieved the highest rice yield, a statistically significant difference compared with organic fertilizer treatment with straw compost and inorganic fertilizer. However, the content of total P, available P, exchangeable Na, and Ca have not improved significantly. Therefore, applying inorganic fertilizers combined with sugarcane filter cakes is an excellent measure to help improve the supply of nutrients from the soil and increase rice yield in the dike land.